Assessing the Evolution of Maritime Strategy in the Asia Pacific - Buddy Suseto; Zarina Othman; Farizal Mohd Razalli (Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
The end of the Cold War has provided an opportunity for scholars to do an in-depth study on the concept of maritime security, especially in the Asia Pacific region. One of the most important but often neglected concepts is maritime strategy which has been developing for centuries. Maritime strategy is designed for states’ survival and to protect their national interests. Nevertheless there is no ‘one size fits all’ concept. Therefore, the purpose of this article is to analyse the similarities and differences between continental states such as the United States, and India, and maritime states such as Indonesia, Japan, Australia, and Singapore in implementing their maritime strategy. In an attempt to present the results, we have reviewed secondary data mainly from the literature written by scholars in the field. Preliminary findings suggests that countries, either continental or maritime states, designed their maritime strategy for national security reasons. States aim to survive in the unknown international political arena. However, domestic and socioeconomic factors such as economic growth, geostrategic interest as well as nature of threats, may have shaped differences among states’ maritime strategy. The emerging non-traditional threats such narcotic trafficking, terrorism and human smuggling, have contributed to the threats for many states, this further justifies the importance of maritime strategy.